(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This study was carried out in a citrus orchard in Adana, Turkey, in 1990-95, to investigate the population fluctuations oftwo scale insects, Aonidiella aurantii (Maskell) and Parlatoria pergandii Comstock, and their parasitoid Aphytis melinus DeBach (Hymenoptera: Aphelinidae). Live and parasitized specimens of both species were counted on 50 randomly selected leaves Sampling was carried out biweekly between May and October and monthly during the remainder of the year. lt was found that the population of A. aurantii was always lower than that of P. pergandii. Average numbers per leaf of P. pergandii and A. aurantii were 9.91 and 2.68, respectively. Populations of two scale insects and their parasitoid fluctuated together. Under the reducing effect of the parasitoid, population levels of the two scale insects always remained low. The parasitization rate of A. aurantii was almost always higher than that P. pergandii, during the study. Average parasitization rate of A. aurantii was 35.79%, while that of P. pergandii was 27.11%.